Focus on vocabulary. 2 : mastering the academic word list / Diane Schmitt; Norbert Schmitt - Schmitt, Diane
"Focus on Vocabulary 2: Mastering the Academic Word List is a research-based vocabulary textbook that gives high-intermediate to advanced students the advantage they need to succeed in academic environments. Through excerpts from college texts and well-crafted exercises, English learners study the Academic Word List - the most frequently used words in academic texts. To help students reach a fuller understanding of the new vocabulary, each chapter provides a series of exercises on word meanings, word families, and collocation."